Metabolomic studies in the inborn error of metabolism alkaptonuria reveal new biotransformations in tyrosine metabolism - Brendan P. Norman; Andrew S. Davison; Juliette H. Hughes; Hazel Sutherland; Peter JM. Wilson; Neil G. Berry; Andrew T. Hughes; Anna M. Milan; Jonathan C. Jarvis; Norman B. Roberts; Lakshminarayan R. Ranganath; George Bou-Gharios; et al. (Genes and Diseases, 2022)
Alkaptonuria (AKU) is an inherited disorder of tyrosine metabolism caused by lack of active enzyme homogentisate 1,2-dioxygenase (HGD). The primary consequence of HGD deficiency is increased circulating homogentisic acid (HGA), the main agent in the pathology of AKU disease. Here we report the first metabolomic analysis of AKU homozygous Hgd knockout (Hgd−/−) mice to model the wider metabolic effects of Hgd deletion and the implication for AKU in humans. Untargeted metabolic profiling was performed on urine from Hgd−/− AKU (n = 15) and Hgd+/− non-AKU control (n = 14) mice by liquid chromatography high-resolution time-of-flight mass spectrometry (Experiment 1). The metabolites showing alteration in Hgd−/− were further investigated in AKU mice (n = 18) and patients from the UK National AKU Centre (n = 25) at baseline and after treatment with the HGA-lowering agent nitisinone (Experiment 2). A metabolic flux experiment was carried out after administration of 13C-labelled HGA to Hgd−/−(n = 4) and Hgd+/−(n = 4) mice (Experiment 3) to confirm direct association with HGA. Hgd−/− mice showed the expected increase in HGA, together with unexpected alterations in tyrosine, purine and TCA-cycle pathways. Metabolites with the greatest abundance increases in Hgd−/− were HGA and previously unreported sulfate and glucuronide HGA conjugates, these were decreased in mice and patients on nitisinone and shown to be products from HGA by the 13C-labelled HGA tracer. Our findings reveal that increased HGA in AKU undergoes further metabolism by mainly phase II biotransformations. The data advance our understanding of overall tyrosine metabolism, demonstrating how specific metabolic conditions can elucidate hitherto undiscovered pathways in biochemistry and metabolism.